The factors that influence the export volume of cocoa beans in Malaysia / Nur Yuhana Norasham (Faculty of Business and Management, 2007)
Cocoa is one of the primary commodities in Malaysia other than palm oil and rubber. In this study, the people will be revealed what are the factors that influence the fluctuation in export volume of cocoa beans such as the prices of cocoa beans itself, land use of cocoa and the changes in exchange rate. The government sometimes uncertainty with the current price of cocoa and difficult to determine the future export performance of cocoa beans in Malaysia because of some factors such as the changes in exchange rate. Not only that, the country is uncertainty for the future cocoa planting area and have to implement some other plan in order to increase the yield of cocoa crop. The objective of this research is to analyze whether there is any relationship between the land use of cocoa, the prices of cocoa beans and the exchange rate with the export volume of cocoa beans. This study uses secondary data that have been gathered from several website such as Malaysian Cocoa Board, Malaysia Department of Statistics, Food and Agricultural Organisation and International Financial Statistics. Then, the data were analyze by using Excel and Statistical Package for Social Science (SPSS) software. After the finding has been done, those identified factors such as land use of cocoa and prices of of cocoa beans had a strong positive relationship with the export volume of cocoa beans. While the exchange rate variable had a negative relationship with the export volume of cocoa beans. Hopefully, the findings of this research can give some reference to the people especially researcher.